A Pugh Matrix framework for selecting effective CALL software in South African schools - Collins, Gary; Ditaunyane, Shoadi Ezekiel (Journal for Language Teaching, 2024)
In recent years, digital technology integration in education, including language learning, has become widespread. South African schools are increasingly acknowledging the benefits of computer-assisted language learning (CALL) applications. Digital tools in educational materials offer advantages such as time efficiency, enhanced accessibility, flexible learning methods, and inclusivity for disabled individuals. However, there’s a lack of appropriate guidelines for assessing and selecting CALL software due to the unique complexities it presents. To address this gap, the study developed a systematic framework, utilising a Pugh Matrix, tailored for South African educational contexts and beyond. This matrix was informed by guiding principles derived from iterative developmental research. A Likert scale survey validated these principles, influencing the weighting of assessment criteria. These criteria encompass curriculum alignment, feedback mechanisms, socio-cultural relevance, affordability, technical considerations, and pedagogical approaches. The developed Pugh Matrix serves as a comprehensive and objective tool for CALL software selection and evaluation. It empowers schools to make informed decisions aligned with their educational goals, instructional methods, technical needs, and budgetary constraints.